Studi Komparatif Metode Discharge Planning pada Self Care Klien Stroke Ischemic - Tarigan, Nusanta; Inayah, Iin; Irianto, Gunawan; Setiawan, Asep; Chan, Chong Mei (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of implementing discharge planning on self-care for ischemic stroke clients at Advent Hospital and Al Ihsan Hospital, Bandung. The method used is quasi-experiment with pretest-posttest with control group design. The sampling technique uses purposive sampling. The results of the research show that the description of Self Care Behavior before and after discharge planning at the Adventist Hospital is that there is an influence of Discharge Planning intervention using flip sheets (audio visual video) and using ROM training tools, with a p-value of 0.01 < 0.05, and Self Description Care Behavior before and after discharge planning at Al Hospital. Ihsan Bandung, There is an effect of Discharge Planning intervention using leaflets with a p-value of 0.01 < 0.05. Furthermore, the description of Self Care Management before and after discharge planning at the Adventist Hospital shows the influence of the Discharge Planning intervention at the Hospital. Advent used a flip sheet (audio-visual video) and used a ROM training tool with a p-value of 0.01 < 0.05 and there was no effect of Discharge planning intervention in the hospital. Al Ihsan used Leaflet with a p-value of 0.71 > 0.05. The conclusion in this research is that there is an influence before and after discharge planning on self-care behavior in hospitals. Adventist and RS. Al Ihsan, and There is an influence before and after discharge planning is implemented on self-care management in hospitals. Advent but there is no influence before and after discharge planning on self-care management in hospitals. Al Ihsan. Keywords: Discharge Planning, Self Care, Self Management, Stroke